Routine use of preoperative breast MRI for patients considered for intraoperative radiotherapy - Choi, Mehee; Small Jr, William; Emami, Bahman (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
This editorial comments on the study by Tallet et al. which reported on the incidence of ipsilateral second breast cancers (BC) detected by preoperative magnetic resonance imaging (MRI) in patients being considered for intraoperative radiotherapy (IORT). Any second BC was detected in 7% of patients; an ipsilateral BC was detected in 4% of patients, precluding them from IORT. The authors comment that in view of detection of a substantial rate of ipsilateral BCs by preoperative MRI, this exam should be used routinely for staging patients being considered for IORT.